THERAPEUTIC DRUG INTOXICATION PATTERN IN THE FEMALE POPULATION DURING THE COVID-19 PANDEMIC IN THE SOUTHEAST SERBIA - Kostic, Emilija; Catic-Djordjevic, Aleksandra; Milosavljevic, Biljana; Simic, Jovana; Vujovic, Maja (Acta medicae Medianae, 2024)
Drugs are the second cause of human intoxication-related mortality and the first in intoxication records. About 1 in 4 individuals around the world will develop mental illness at some point in their lifetimes. Viral outbreaks, such as the coronavirus disease (COVID-19) pandemic, are associated with short-term and long-term psychological and societal distress. The current review of poisoning patterns in southeast Serbia is imperative. A retrospective cross-sectional study was carried out for two years, from March 2020 to March 2022, to evaluate the prevalence and trends of pharmaceutical drug poisonings. Retrospective data on poisoning cases was collected from the medical records section of the Toxicological Laboratory of the Institute of Forensic Medicine in Niš. Of the 310 cases, 59.35% of intoxications were observed in the female population. The most significant female predominance was observed in the age category 12–19 years (75%). In all age groups over 51, there are more female intoxications than male intoxications by a factor of more than 2.17. In age category 12–19, the most commonly detected drug class was sedatives, followed by analgesics and antiepileptics. In the population over 51, the most frequently detected drug classes in intoxication were sedatives (32.67%), followed by drugs for cardiovascular diseases (15.84%), antiepileptics (13.86%), and antidepressants (11.88%). Women over 51 and in the adolescent age category should be the target group for education and raising awareness about mental health. The prescription of sedatives should always be carefully considered, as this class of drugs is the most common in poisoning.
Keywords: drugs; intoxication; COVID-19; female